Optimizing Nutrient Intake as a Preventive Effort in Overcoming Mental Health Problems: A Literature Review - Nur Ainnah Mulyadi (Journal of Nutrition and Health Care, 2024)
Mental health has become an increasing global concern in recent years. Various approaches have been developed to treat mental health problems, including pharmacological interventions and psychotherapy. However, the role of nutrition in supporting mental health is still often overlooked. This literature review aims to explore the relationship between nutritional intake and mental health, as well as identify strategies for optimizing nutrition as a preventive measure in overcoming mental health problems. The methodology used was a systematic review of scientific articles published in the last 10 years, with a focus on studies examining the relationship between nutrition and mental health. The review results show that several nutrients have an important role in brain function and neurotransmitter regulation, including omega-3 fatty acids, B complex vitamins, magnesium, and zinc. Deficiencies in these nutrients have been linked to an increased risk of mental disorders such as depression, anxiety, and bipolar disorder. Nutritional intervention studies show promising results in improving the symptoms of mental disorders and the quality of life of patients. Identified strategies for optimizing nutrient intake include (1) increasing consumption of nutrient-rich foods such as fish, green vegetables, nuts, and whole grains; (2) supplementation of certain nutrients in individuals at risk of deficiency; and (3) overall dietary modification, such as adopting a Mediterranean diet. Although these results are promising, further research is needed to confirm the effectiveness of nutritional interventions on a larger scale and in diverse populations. In addition, there is a need to develop practical guidelines for health professionals in integrating nutritional approaches into mental health management. In conclusion, optimizing nutritional intake has the potential to be an effective and relatively safe preventive strategy for overcoming mental health problems. This approach can be integrated into mental health promotion programs and clinical interventions to improve overall health outcomes.